UNUSUAL PRESENTATION OF THROMBOEMBOLIC DISEASE IN A HOSPITALIZED PATIENT WITH A COVID-19 INFECTION: A CASE REPORT - Gigovska Dimova, Irena; Buklioska Ilievska, Daniela; Nedeska Minova, Natasha; Terzievska, Keti (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
With no ideal specific therapy confirmed by the science community, and many low income countries barely being able to obtain a sufficient number of vaccines, as well as the long-term mental health impact, the COVID-19 infection makes for a worldwide health and global problem. A COVID-19 positive patient was admitted due to poor condition, malaise and bilateral interstitial pneumonia with borderline oxygen saturation of 94%, hypoxemia with pO2 of 64mmHg, and elevated C reactive protein (CRP) of 70. The patient was put on oxygen support of 3l/min, and started parenteral antibiotic and LMWH in prophylactic doses - a combination that primarily improved the patientâ€™s condition.  Three days after hospitalization marked shortness of breath with a drop in oxygen saturation of 62% referred. With further increasing of the oxygen flow, and a transfer to ICU, gas pressures showed significant worsening and the patient was put on mechanical support with a CPAP mask. Despite adding pulsed doses of potent corticosteroid, rapid acting insulin for blood glucose control, and administerring convalescent plasma and parenteral nutrition, the CRP levels were increasing and oxygen was decreasing. Hypotensive, tachycardic and with reduced urine output, the patient was intubated and set up on IPPV mechanical support. Vasopressor stimulation didnâ€™t improve the diuresis and elevation of degradation products followed, as well as elevation of the troponin and cardiospecific enzymes - non of which was caused by sepsis. Eight days after admission, the left arm presented as pale, cool and cyanotic. Fully deteriorated laboratory findings of multiple organ system failures (MOFS) were undoubtable; with the oxygen levels incompatible of life, and a CT scan with ARDS presentation, a continuous heparin infusion was the only solution. At the beginning, nothing indicated the deleterious outcome; however, with a highly unusual presentation of arterial thrombosis, the upper limb gangrene became too much and the patient died. COVID-19 is primary a respiratory infection, but the virus can affect other organs and systems, with some very rare presentations and deleterious outcomes. Keywords: COVID 19, limb ischemia, thromboembolism, COVID-19-associated coagulopathy, multiple organ system failure. https://doi.org/10.55302/JMS2143094gd